P1-S6.43 HPV vaccine coverage among high-risk women: racial and socioeconomic disparities and barriers. (10th July 2011) - Niccola, L; Mehta, N; Julian, P; Bilinski, A; Sosa, L; Meek, J; Hariri, S; Markowitz, L; Hadler, J
Abstract : Background: Human papillomavirus (HPV) is a necessary cause of cervical cancer and two vaccines are recommended for routine use among females ages 11–12 years with catch-up through age 26. Reducing disparities in cervical cancer will depend on achieving adequate vaccine coverage among racial and ethnic minorities and low-income women. The purpose of this analysis was to describe racial, ethnic, and socioeconomic differences in HPV vaccine coverage and identify barriers to catch-up vaccination. Methods: Telephone interviews were conducted among women diagnosed with precancerous cervical lesions and reported to the CT Department of Public Health for routine surveillance during 2008–2010. The sample consisted of 269 women ages 18–27 years (age-eligible for catch-up vaccination after licensure) including 77% white, 15% black, and 17% Hispanic; median age was 23 years. Results: Overall, 43% of women reported having received ≥1 dose of HPV vaccine (mean age at vaccination 22 years). Publicly insured and uninsured women were significantly less likely than privately insured women to have received vaccine (23% and 15% vs 52%, p<0.05 for both), and black women were marginally less likely to receive vaccine compared to white women (31% vs 48%, p=0.06). There was no significant difference for ethnicity. The most common self-reported barrier to vaccination was lack of provider recommendation (25%). Other common self-reported reasons were previous HPV diagnosis (20%) and being too old (15%). Women who did not discuss HPV vaccine with a provider were more likely to have not received vaccine compared to women who discussed vaccine (95% vs 44%, p<0.001) see Abstract P1-S6.43 Figure 1 . Conclusions: Provider interventions may be necessary to assure catch-up vaccine is offered to eligible women. A common reported barrier was being too old, yet all women in this sample were age-eligible for vaccination. Previous HPV infection was another common barrier, yet this is not a contraindication for vaccination to protect against infection from other HPV types. In particular, greater efforts are required to administer catch-up vaccine to low-income and black women. Providing vaccine for underinsured women in this age group will be a challenge because they are not eligible for some state or federal vaccination programs (eg, Vaccines For Children).